2011
DOI: 10.1159/000327009
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress Induces the Release of an Endothelial Elastase: Role in Integrin α<sub>v</sub>β<sub>3</sub>-Mediated FGF-2 Release

Abstract: Background/Aims: Laminar shear stress is an important stimulus in the endothelium-dependent control of vascular tone and of vascular remodeling processes. Based on previous studies demonstrating integrin-mediated release of fibroblast growth factor 2 (FGF-2), we investigated whether shear stress-induced integrin activation requires the involvement of an extracellular protease. Methods: Cultured porcine aortic endothelial cells (PAEC) were exposed to laminar shear stress (16 dyn/cm2), whereas static … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Previous studies have implicated αvβ3 in the regulation of P38 MAPK signaling in melanoma and endothelial cells [47, 48]. Therefore, to begin to assess possible mechanisms to account for the altered IGFBP-4 in M21 cell variants, we first examined whether changes in αvβ3 expression in M21 cells were associated with altered MAP kinase levels.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have implicated αvβ3 in the regulation of P38 MAPK signaling in melanoma and endothelial cells [47, 48]. Therefore, to begin to assess possible mechanisms to account for the altered IGFBP-4 in M21 cell variants, we first examined whether changes in αvβ3 expression in M21 cells were associated with altered MAP kinase levels.…”
Section: Resultsmentioning
confidence: 99%
“…Such interactions may be important for the activation of integrins as well as for the regulation of kinase activity of these growth factors [49]. Even if this type of interaction has not yet been demonstrated with FGF-2, several reports suggest that beta-3 integrin and FGF-2 are involved in common metabolic pathways in vascular or ocular cells [50][52]. Whereas FGF-2 itself is known to be an important actor in wound healing [53], it was demonstrated that beta-3 integrin is also required for wound angiogenesis [54].…”
Section: Discussionmentioning
confidence: 99%
“…Of note in this regard, PKCε can affect activity in the mitochondrial electron transport chain (Nowak et al, 2004; Costa and Garlid, 2008); and it has been shown, in other cells, that PKCε can translocate to mitochondria (Joseph and Levine, 2006; Ferrari and Levine, 2010) where it can phosphorylate proteins including members of the mitochondrial electron transport chain complex (Costa and Garlid, 2008). Since endothelial cells can be activated by mechanical stimuli such as shear stress (Binti Md Isa et al, 2011; Hennig et al, 2011) signaling via the mitochondrial electron transport chain in endothelial cells (Ali et al, 2004; Zhang et al, 2005) can lead to the release of a number of pronociceptive mediators (e.g., prostaglandins, ATP, nitric oxide, endothelin-1, platelet-derived growth factor, interleukin-1, interleukin-6 and ROS (Corl et al, 2008; Iwata et al, 2010; Laskin et al, 2010), and mechanical stimulation of the endothelial cell releases ATP (Milner et al, 1990), the endothelial cell is a compelling candidate for mediating SIEH.…”
Section: Discussionmentioning
confidence: 99%